2007
DOI: 10.1017/s0014479707004978
|View full text |Cite
|
Sign up to set email alerts
|

GENOTYPIC DIFFERENCES IN THE GROWTH OF BANANAS (MUSA SPP.) INFECTED WITH MIGRATORY ENDOPARASITIC NEMATODES. 1. ROOTS

Abstract: The effects of nematodes on root morphology and the association of root characteristics with resistance to nematodes of seven banana varieties were investigated in two experiments. Banana plants were grown in controlled conditions within polytunnels and harvested on three occasions for the measurement of root morphology and biomass. Varieties differed in their resistance to nematodes, from resistant (Yg Km5, FHIA 17, FHIA 03) and partly resistant (FHIA 01, FHIA 25) to not resistant ((FHIA 23, Williams). Nemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In a controlled environment experiment in the UK, Kalorizou et al . (2007) found that resistance to nematodes (a major constraint to banana reduction in some places as a result of the damage they cause to primary roots) was associated with two clones (AAA and AABB) with greater root mass and more and larger primary roots than the other five cultivars tested. In Uganda (5°13′N alt.…”
Section: Crop Developmentmentioning
confidence: 99%
“…In a controlled environment experiment in the UK, Kalorizou et al . (2007) found that resistance to nematodes (a major constraint to banana reduction in some places as a result of the damage they cause to primary roots) was associated with two clones (AAA and AABB) with greater root mass and more and larger primary roots than the other five cultivars tested. In Uganda (5°13′N alt.…”
Section: Crop Developmentmentioning
confidence: 99%